Aphorisms of masquism : the wisdom of the fundamental grammar of life and a religion for democracy - Vaidyanathan, Remaji (Cambridge Scholars Publishing, 2017)
"This book represents the monumental work of Swami R. Vaidyanathan, who was a research student at Cambridge under Lord Rutherford from 1934 to 1938. Through nine aphorisms, it presents a complete and unique philosophy. It is an independent work, not based on any book or person or symbol, and offers a new view of a way of living and a new conception of self-regarding. Though the main aim of this philosophy is the reduction of human suffering and the promotion of world welfare, the foundation it gives to establish the philosophy to achieve that aim represents a complex network of ideas that are all amazingly interwoven and interrelated"--Back cover